INTERNALISASI PEMBELAJARAN PAI PADA ANAK BERKEBUTUHAN KHUSUS DI SLBN TANAH GROGOT TINGKAT SMPLB - Rahim, Abdan; Mushaffa, Siti Mauzunim (FIKRUNA Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2022)
This study aims to determine: (1) Internalization of PAI learning for children with special needs at the SMPLB Tanah Grogot SLBN level. (2) Supporting and inhibiting factors when internalizing PAI learning for children with special needs at the SMPLB Tanah Grogot SLBN. This type of research is field research, using data collection techniques, namely, observation, documentation, and interviews with the parties involved in this study. From the results of research at the Tanah Grogot SLBN, researchers can draw conclusions: first, the internalization of PAI learning for children with special needs at the Tanah Grogot SLBN SMPLB level that the internalization process differs between mentally retarded, physically disabled, deaf, and autistic. Both in terms of learning methods or learning media. Then learning PAI online also has a good influence in terms of learning evaluation, effectiveness, and psychology for children with special needs SLBN Tanah Grogot. Second, almost 90% of the inhibiting and supporting factors for the internalization of PAI learning in children with special needs come from external sources. From the inhibiting factors, namely lesson plans that are not carried out properly, minimal books and learning that is not carried out face-to-face. As for the supporting factors, namely from parents and experienced teachers.